Uji LC50 Limbah Tahu Terhadap Ikan Nila (Orechromis Niloticus) Umur 2 Bulan di Banjarbaru - Hardiono Hardiono; Rahmawati Rahmawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2014)
Abstract: LC 50Test of Tofu Waste Water to Tilafia (Orechromis niloticus) aged 2 months in Banjarbaru. Tofu industrial wastewater with a low pH, 0 mg/l DO and a temperature of 32°C when discharged without treatment into receiving water bodies will lead to the death of aquatic biota so acute toxicity tests need to be done. This study aims to determine the LC50 of the waste out in tilapia (Oreochromis niloticus). This study used an experimental method, posttest design with a control group. Samples were taken randomly in waste outlet in Banjarbaru, then toxicity tests performed with various of toxicant concentrations and exposure time at tilapia of 2 months age. Based on the initial results of toxicity tests, the lowest concentration that causes 100% dead of tilapia is 20%, so that the concentration of industrial wastewater know that will be used in the acute toxicity tests are: 4, 8, 12, 16 and 20%. Parameters wich were controlled are pH, temperature and DO. Probit analysis using SPPS was used to determined LC50. The results showed that LC50 for exposure time: 24, 48 and 72 hours are 3.80 up to 11.35%, 3.67 s.d 14.30% and 3.38 up to 12.10% particularly. Correlation analysis showed the characteristics of pH and DO in the tofu industrial wastewater affects the LC50. Decrease of DO and pH, LC50 would decrease. The study is expected as input to information and pollution control and waste out policy decisions in order to make local regulations maintained environmental sustainability. For further research can complement parameters Ammonia levels and turbidity in the water that affect the survival of fish, in addition to the pH, DO and temperature of the water.Keywords : LC50 test; tofu waste water; Tilafia (Orechromis niloticus) of 2 months aged.